Kampanye Zero Waste Nature Republic Indonesia dalam Mendukung Praktik Sustainable Beauty - Akbar, Dinul Fajri; Ramonita, Latifa (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
The sustainable beauty trend encourages business actors in the beauty industry to pay attention to environmental sustainability through, innovation of environmentally friendly products and the implementation of a holistic sustainability communication strategy. Zero Waste: Refresh, Recycle and Repeat campaign is a concrete practice of the Nature Republic Indonesia in disseminating long-term sustainability messages through a dynamic communication strategic approach. The purpose of this study is to identify the implementation of the strategy and the challenges encountered in the campaign program, to achieve sustainable beauty. This study uses the concept of a seven-stage PR campaign strategy. This research method is a descriptive qualitative approach with a post-positivist paradigm. The results show that the implementation of the campaign program can increase environmental awareness and active collaboration of the target audience in preserving the earth. Then, it expands the visibility of the Nature Republic brand in Indonesia through a positive response from the target audience. It also shows quite good support for sustainable beauty through clear sustainability initiatives. There are technical obstacles and a lack of human resources. Therefore, in addressing these obstacles, Nature Republic Indonesia is improving its strategic and comprehensive communication and coordination approach to relevant stakeholders.